Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 1- Parity of blood seeking Anopheles (Kerteszia) in South-Eastern Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Almério de Castro Gomes (Universidade de São Paulo, 1993)
Populations of Anopheles (Kerteszia) were sampled fortnightly over a one-year period (August 1991 to July 1992) at Ribeira Valley, S. Paulo State, Brazil. Indoor and outdoor collections were made on human bait at evening crepuscular period. The Polovodova technique for age grading was applied to 3,501 females of Anopheles cruzii and to 416 females of An. bellator. That sample represented 34.4% of the total number of mosquitoes collected. The most abundant species found was An. cruzii. However, An. bellator showed an endophagy that was almost three times greater than that of An. cruzii. The overall parous rate was 25.4% and uniparity was practically dominant one. A proportion of 26.9% of An. cruzii and 12.0% of An. bellator were found to be uniparous. Only three outdoor females of the former species (0.1%) showed biparity. Parity of An. cruzii was higher in females caught outdoors than in those caught indoors. Nevertheless, 497 nulliparous females examined (417 cruzii and 80 bellator) had ovaries that had advanced to Christophers and Mer stages III to V. These results imply that these females had already practised hematophagy. Relating these results to those from the parous females, a high statistical significance was found, leading to the conclusion that gonothophic discordance is a common pattern among these anophelines. Further, these results obtained with human bait catches strongly suggest that nearly 38.0% of these host-seeking females had already taken at least one previous blood-meal. So it is possible that enough time could thus be available for the plasmodian development in the vectors.